Fostering Synergistic Collaboration: A Triple Helix Model for Integrating Educational Management, Digital Pedagogy, and Sharia Financial Literacy in Indonesian Islamic Economics Higher Education - Kurniawan, Muhammad Iman; Syam, Aldo Redho; Kamilah, Athia Nur; Rahman Zh, Miftah Hur; Akbar, Rifaldi Nurul (Universitas Negeri Jakarta, 2025)
Background The convergence of educational transformation, technological advancement, and the preservation of ethical values presents a significant challenge for higher education institutions, particularly in delivering Islamic economics education that remains faithful to its foundational principles amidst the Society 5.0 era. Purpose This study investigates the convergence of educational management strategies, technology-enhanced pedagogy, and Islamic economics principles within Indonesian higher education institutions to understand how digital transformation reshapes the pedagogical ecosystem of Islamic economics education. Design/method/approach Employing an explanatory sequential mixed-methods design combining quantitative surveys (n = 387) and qualitative semi-structured interviews (n = 24) across six Islamic higher education institutions, the research examines the relationships between digital transformation and educational outcomes in Islamic economics. Results The quantitative findings reveal that technology-integrated educational management significantly predicts student learning outcomes in Islamic economics (β = 0.47, p < .001) and sharia financial literacy (β = 0.39, p < .001). Structural equation modeling indicates that digital pedagogical competence mediates 34.2% of the variance in student engagement with Islamic finance concepts. Qualitative thematic analysis identifies four emergent themes: institutional readiness for digital transformation; alignment of the curriculum with Islamic values and technological innovation; the role of learning management systems in fostering sharia-compliant understanding of financial matters; and stakeholder perceptions of technology-mediated Islamic economics instruction. Contribution/value The study proposes an integrative Triple Helix framework, Educational Management, Educational Technology, and Islamic Economics (EM-ET-IE), offering a novel theoretical contribution for designing sustainable, value-based digital learning ecosystems. These findings carry significant implications for policymakers, educational administrators, and curriculum designers seeking to reimagine Islamic economics education while preserving its foundational ethical principles.